1996
DOI: 10.1177/004728759603400407
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Plog's Psychographic Travel Model within a Student Population

Abstract: Correlation analysis is used to examine the association between Plog's instrument, underlying theoretical constructs, and actual travel behavior. Cross-validation of Plog's model was achieved through three personality trait measures and a modified Nickerson scale. This study broadens the behavioral foundations of psychographic research within the travel literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…They are not as adventurous as people in the West, who are in general allocentrics. Eight travel preferences were examined based on the attributes of allocentric and psychocentric travel preferences suggested by several studies (e.g., Goeldner, Ritchie & McIntosh, 2000;Griffith & Albanese, 1996;Nickerson & Ellis, 1991). The items were measured on a 7-point Likert-type scale, with 1 representing "not at all desirable" and 7 representing "extremely desirable" (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are not as adventurous as people in the West, who are in general allocentrics. Eight travel preferences were examined based on the attributes of allocentric and psychocentric travel preferences suggested by several studies (e.g., Goeldner, Ritchie & McIntosh, 2000;Griffith & Albanese, 1996;Nickerson & Ellis, 1991). The items were measured on a 7-point Likert-type scale, with 1 representing "not at all desirable" and 7 representing "extremely desirable" (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers (Pitts & Woodside, 1986;Pizam, 1999;Kim & Lee, 2000) have used the psychographic approach to understand tourist behavior from different cultures, since demographics and situational variables such as travel patterns are not sufficient when studying tourist behavior (Griffith & Albanese, 1996). For example, Kim and Lee used visitors' cultural orientations of individualism and collectivism to understand the differences in travel motivations and found that individualists are more likely to seek novelty when traveling, while collectivists are more likely to travel to be with family.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of researchers today agree that despite the relative attractiveness and intuitive appeal of Plog's original model, it has limited practicality as a managerial decision support tool (Abbey 1979;Chon and Sparrowe 2000;Litvin 2006;Griffith and Albanese 1996 ). Findings from the current research undertaking go some distance in mitigating some of the conspicuous criticisms leveled at Plog' s original model.…”
Section: Discussionmentioning
confidence: 92%
“…They were able to validate much of Plog's theory, and they found that travel preferences were heavily influenced by types of travel destinations and types of family experiences from when participants were growing up (Griffith & Albanese, 1996). If trips during childhood have a large bearing on travel preferences during adulthood, then the high school band, orchestra and choir trip can indeed have a role in building those preferences.…”
Section: Travel Theorymentioning
confidence: 93%
“…As a means of testing Plog's theory, Griffith and Albanese (1996) studied 145 undergraduate students who were in the young single stage of their family life cycle. They were able to validate much of Plog's theory, and they found that travel preferences were heavily influenced by types of travel destinations and types of family experiences from when participants were growing up (Griffith & Albanese, 1996).…”
Section: Travel Theorymentioning
confidence: 99%